Sustainable Leadership Model for Female Principals - Toni, Hariya; Deswita, Melda; Zuhdi, Ahmad (AGENDA: Jurnal Analisis Gender dan Agama, 2022)
This research is a literature research that aims to describe how to anticipate emerging threats for business continuity, and even humans in the future? In this case, there is the concept of Sustainability Leadership, which can simply be interpreted as leadership in an organization that is concerned with sustainability or sustainability in the long term, both in business and the environment in which humans live. In this case, the leadership of men and women is influenced by several factors that make leaders able to apply leadership effectively. These factors are emotional and social, ways of thinking, communicating, orientation, physical nature, and roles in the family (M. Saunan Al Faruq, 2016). Women have dimensions of communal behavior that tend to think about the welfare of their subordinates and emphasize interaction, as well as facilitating subordinates. While men are more likely to have an agentic dimension that is assertive, goal-oriented and tends to be domineering